Creation of the Institute of Medical Law as its Sub-Institute (Sub-Directorate) in the Legal System of Ukraine - Gorbach, Oksana V.; Yaroshenko, Iryna S.; Skoryk, Vadim O. (Cuestiones Políticas, 2020)
The current stage of training and development of medical law is characterized by discussions on the allocation of medical law in a separate law institute, all in the context of the global COVID-19 crisis. This article aims to identify the concept of medical law institute, including the justification for the need to establish a medical law institution and the consideration of sub-institutes (sub-branches) of medical law. The main method for the study of this topic was the method of analysis, which allows to comprehensively consider the sub-institutes of medical law and the reasons for the separation of the institute of medical law. The document presents the classification of the drug circulation sub-institute (sub-branch) and reveals the components of the structure of medical law. In conclusion, it highlights that, the formation and development of medical law must be based on the following principles: first, it must have the essential characteristics of the law; and, secondly, it must arise and exist in the field of medical professional activity: in the science, practice, ethics and deontology of medical personnel, the rules and procedures of medical institutions.